(untitled) (TRIM. Tordesillas, revista de investigación multidisciplinar, 2022)
Abstract: As rational and discursive creatures, our relationship with the world is necessarily articulated through a certain understanding of both ourselves and what surrounds us. This means, in other words, that our experience is not the result of mere perception, but of a construction that guides and limits, through deliberate processes or not, both our actions and our beliefs and convictions. Faced with these considerations, we can ask ourselves some highly relevant philosophical questions: how is this constitutive understanding of what is human articulated? Is it a necessarily conceptual process? Or is there a mode of relationship with reality prior to the plane of concepts? Are we capable of carrying out thoughtless actions in which our rationality is not at stake? Such questions cross an intense philosophical debate that extends to the present, initiated by the philosophers Hubert Dreyfus and John McDowell. The discussion focuses on the ultimate nature of our exchange with the world and with others, and on the possibilities (or not) of establishing a contact that is articulated outside the rational and conceptual dimension of our structures. In the present work, our interest will be to analyze and describe the central positions maintained by both authors with three fundamental objectives. On the one hand, to specify the theoretical disagreement between both positions, understanding the different theoretical commitments that they entail. On the other hand, to maintain that Dreyfus’s anti-intellectualist argument is at odds with a series of familiar phenomena, indicating a set of considerations for which McDowell defends a better position. Finally, to point out the difficulties inherent in the interpretation that Dreyfus makes of Heidegger’s phenomenology, in order to propose a hermeneutical alternative that finds the German philosopher in a space much closer to McDowell’s conceptualist conception. Our general hypothesis will be that Dreyfus’ proposal according to which our primary way of relating to the world is prior to the conceptual plane is unfeasible due to the individualistic assumptions on which it rests. In this direction, we will defend the idea that a conceptualist approach does justice to the idea that acting and knowing is only possible in a community of rational agents, neither human action nor knowledge being possible beyond the limits of the relationship with other discursive and rational beings.